A chiral spirobifluorene-based bis(salen) zinc(ii) receptor towards highly enantioselective binding of chiral carboxylates. Issue 12 (4th March 2021) - Ikbal, Sk Asif; Sakata, Yoko; Akine, Shigehisa
Abstract : A new chiral receptor based on two salen zinc(ii ) complex units and a spirobifluorene linker enantioselectively binds chiral carboxylate guests. Abstract : We have designed a new chiral receptor based on two salen zinc(ii ) complex units connected with a spirobifluorene framework. The chiral receptor is proven to enantioselectively bind chiral carboxylate guests and the differences between the binding constants of enantiomeric guests were up to more than one order of magnitude.